European Society for Immunodeficiencies (ESID) and European Reference Network on Rare Primary Immunodeficiency, Autoinflammatory and Autoimmune Diseases (ERN RITA) complement guideline: deficiencies, diagnosis, and management - Brodszki, Nicholas; Frazer-Abel, Ashley; Grumach, Anete S.; Kirschfink, Michael; Litzman, Jiri; Perez, Elena; Seppänen, Mikko R. J.; Sullivan, Kathleen E.; Jolles, Stephen (Journal of clinical immunology, 2020)
This guideline aims to describe the complement system and the functions of the constituent pathways, with particular focus on primary immunodeficiencies (PIDs) and their diagnosis and management. The complement system is a crucial part of the innate immune system, with multiple membrane-bound and soluble components. There are three distinct enzymatic cascade pathways within the complement system, the classical, alternative and lectin pathways, which converge with the cleavage of central C3. Complement deficiencies account for ~5% of PIDs. The clinical consequences of inherited defects in the complement system are protean and include increased susceptibility to infection, autoimmune diseases (e.g., systemic lupus erythematosus), age-related macular degeneration, renal disorders (e.g., atypical hemolytic uremic syndrome) and angioedema. Modern complement analysis allows an in-depth insight into the functional and molecular basis of nearly all complement deficiencies. However, therapeutic options remain relatively limited for the majority of complement deficiencies with the exception of hereditary angioedema and inhibition of an overactivated complement system in regulation defects. Current management strategies for complement disorders associated with infection include education, family testing, vaccinations, antibiotics and emergency planning.